PENGARUH DESAIN RUANG TERHADAP KONDISI ALIRAN UDARA DALAM UPAYA PRESERVASI KARYA SENI RUPA PADA MUSEUM GALERI NASIONAL INDONESIA - Hendrico, Bartholomeus; Enggar Sari, Wulani (Jurnal Riset Arsitektur, 2025)
Abstract - Preservation efforts can be done through active or passive mechanisms to safeguard and preserve. The existence of the environment in the gallery space, which includes features of humidity, temperature, and airflow, has a great influence on the preservation factor for works of art, where this matter influences the sustainability of the existence of works of art that are stored. Fine arts museums in Indonesia are frequently found to be lax in their efforts to conserve what should have become normal practice, perhaps causing damage to existing pieces of art. This study employs quantitative and experimental methods, including Autodesk CFD simulation trials that generate a description of the existing condition of the study object and its relationship to the influence of work of art preservation, as well as simulation trials of the influence of existing design developments that are aligned and compared with work preservation theory guidelines. art. Field observations and literature searches were used to acquire data. Data are organized according to research variables, which include features of artwork preservation in museum settings, humidity-temperature-air flow, artwork preservation support systems, and space design development. The analytical technique employs distribution simulation in conjunction with the idea of guidelines for the preservation of works of art, as well as simulations for optimizing the design of interstitial spaces, which aid research in developing scope for better preservation. The research found that the performance of the design of the layout of the museum space might influence the existence of the gallery space's climatic conditions, which affect aspects of preservation efforts and the condition of the works of art in it. The architecture of the museum's spatial organization must be able to prevent as much of the impact of the external climate as possible and establish stable indoor circumstances so that climate changes do not occur, undermining efforts to preserve pieces of art. It was discovered that the optimum design of the implementation of the interstitial space or airlock can be a solution to the preservation effort problem, and has been shown to be capable of producing climatic conditions in interior spaces or structures that tend to fall and are in a constant or stable state. The overall implementation of the inter-room design can reduce the presence of airflow by 99.54% and the temperature by 2.04 'C, decrease airflow and temperature from the outer enclosure to the airlock lobby by -83.67% and -4.62%, internal airlock space by -98.26% and -5.25%, and museum space by -99.54% and -5.79% Keywords: Preservation, works of art, humidity, temperature, airflow, spatial, arrangement, constant